2003
DOI: 10.1023/a:1027383729767
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Aminopeptidase N (APN/CD13), a Zn2+-dependent ectopeptidase, is localized on the cell surface and functions as a transmembrane protein. Increased expression and activity of APN have been postulated to correlate with the aggressive behavior of several tumor types. In this study, the osteosarcoma cell line MNNG/HOS was stably transfected with an expression vector capable of expressing the antisense transcript of APN. Four stably transfected clones, the control clones and parental cells were characterized. Stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Aoki et al reported CD13 expression on tumor cells with variability according to the STS subtype in a small series [26] , but there is no investigation published differentiating between vascular and perivascular presence of CD13 versus presence of CD13 on sarcoma cells in human tissues. CD13 has been described to contribute to osteosarcoma migration and invasion [27] , [28] , but overall, only little is known on the functional role of CD13 in sarcoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Aoki et al reported CD13 expression on tumor cells with variability according to the STS subtype in a small series [26] , but there is no investigation published differentiating between vascular and perivascular presence of CD13 versus presence of CD13 on sarcoma cells in human tissues. CD13 has been described to contribute to osteosarcoma migration and invasion [27] , [28] , but overall, only little is known on the functional role of CD13 in sarcoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…In former studies, it has been shown that ANPEP/CD13 enzymatic activity aids invasion of HGOS cells, a process contributing to the aggressiveness of the disease. 11 , 14 16 , 46 These observations can be attributed to the pivotal role of ANPEP/CD13 in remodeling the extracellular matrix and promoting angiogenesis, two processes implicated in HGOS metastasis. Moreover, in our study, biopsy samples of poor responders showed higher levels of ANPEP mRNA expression in comparison with that of good responders.…”
Section: Discussionmentioning
confidence: 99%
“… 11 13 In osteosarcoma, ANPEP has been identified as a driver of cell migration and invasion. 14 16 The aminopeptidase activity of ANPEP has been associated with the activation of PI3K and MAPK pathways, 14 , 15 known contributors to HGOS pathogenesis and metastasis. 17 , 18 High-ANPEP expression was linked to poor survival in osteosarcoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…CTB invasive ability was assayed by using transwell inserts according to the method reported by Kido et al [23,24]. SMCs were placed in the transwell lower chamber, and CTBs in the transwell upper chamber.…”
Section: Methodsmentioning
confidence: 99%